Optimalisasi Desa Wisata dalam Meningkatkan Ekonomi Masyarakat di Desa Maguwan Sambit - Restiani, Restiani; Susanto, Hanafi Hadi (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Beji Gondang is a beautiful, comfortable, clean and beautiful tourist spot, this area is also equipped with several photo spots. Beji Gondang is also an economic center for the community. The potential for tourism development as employment has had a high enough impact on the surrounding community to sell food and beverages. Along with the development of tourism, it has brought its own consequences, especially in tourist destinations and local communities. This research uses a discriminatory qualitative method, which describes the data found in the field to become new finding data. The results of this study show that the presence of tourism is able to accelerate economic growth and provide employment, one of which is tour guides, parking attendants, photographer services, increase income, improve living standards, and stimulate other productive sectors that the growth of business and work opportunities due to tourism causes demand for labor to increase. The more tourists who visit, the more types of businesses that grow in tourist areas so that more jobs are created. This shows that tourism has great potential in providing jobs for workers who need new jobs.